C-Shaped Canal System in Mandibular Second Molars Evaluated by Cone-Beam Computed Tomography in an Argentinean Subpopulation (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: C-shaped canal; dental anatomy; mandibular second molar; cone-beam computed tomography